Foundation phase learners' and teachers' attitudes and experiences with the Rwandan language-in-education policy shifts - Niyibizi, Epimaque (My University, 2015)
This study entitled “Foundation Phase Learners’ and Teachers’ Attitudes and Experiences with the Rwandan Language-in-Education Policy Shifts” is a contribution to the field of language-in-education policy. It focuses on the Rwandan foundation phase (i.e. lower primary school) learners and teachers. It examines their attitudes and experiences towards the Rwandan unfamiliar consecutive language-in-education policy shifts whereby the former trilingual medium shifted to initial English medium (initial submersion) in 2008, and then switched to Kinyarwanda medium (sudden transfer) in 2011, in the Rwandan lower primary schools. While several language attitudes studies in the existing literature have mainly concentrated on attitudes to individual languages, there is dearth of attitudes research studies which uncover the true nature of attitudes towards different language types, such as exoglossic or endoglossic languages within the African context (Adegbija, 1994, p. 52) or attitudes to balanced bilingualism (Baker, 1992, p. 3). Thus, this study contributes to addressing these gaps by investigating the learners’ attitudes and experiences towards initial submersion they started with English medium in grade 1, and then shifted to sudden transfer with Kinyarwanda medium in grade 2 and 3; within an African endoglossic and unicultural country. Drawing insights from the “Concurrent Embedded Strategy” of the mixed methods (Creswell, 2009, p. 210), qualitative and quantitative methods of data collection and analysis were used. This study was conducted among a sample of 324 informants which comprised 300 learners, 18 teachers and 6 principals, who were selected from 6 lower primary schools in Rwanda. The striking finding is that in addition to the universal preference for English medium, the Rwandan rural school learners and teachers showed more positive attitudes towards the shift to an African endoglossic language (Kinyarwanda), which debunks the folklore in the existing literature that exogenous languages are preferred over indigenous languages.
THESIS Submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Applied Language and Literacy Education Faculty of Humanities School of Education University of the Witwatersrand, Johannesburg, South Africa